Hemorrhagic Stroke - Boccardi, Edoardo; Cenzato, Marco; Curto, Francesco; Longoni, Marco; Motto, Cristina; Oppo, Valentina; Perini, Valentina; Vidale, Simone; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides detailed practical guidance on the management of hemorrhagic stroke in the clinical settings encountered in daily practice. Real-life cases are used to depict a wide range of clinical scenarios and to highlight significant aspects of management of hemorrhagic stroke. In addition, diagnostic and therapeutic protocols are presented and helpful decision-making algorithms are provided that are specific to the different professionals involved in delivery of stroke care and to differing types of hospital facility. The coverage is completed by the inclusion of up-to-date scientific background information relevant to diagnosis and therapy. Throughout, the approach adopted is both practical and multidisciplinary. The book will be of value for all practitioners involved in the provision of stroke care, and also for medical students.
Diagnosis and therapy in the acute phase of hemorrhagic stroke: latest developments -- Clinical cases -- Clinical organizational pathways for hemorrhagic stroke -- Differentiated decisional algorithms.
Keywords: Medicine; Emergency medicine; Neuroradiology; Neurology; Neurosurgery; Medicine & Public Health; Neurology; Emergency medicine; Neurosurgery; Neuroradiology